Demonstration of the Need for Cardiovascular and Pulmonary Normative Data for Cancer Survivors - Schneider, C. M.; Repka, C. P.; Brown, J. M.; Lalonde, T. L.; Dallow, K. T.; Barlow, C. E.; Hayward, R. (International Journal of Sports Medicine, 2014)
Despite evidence that cancer and its treatments severely reduce cardiorespiratory fitness (CRF), normative data for cancer survivors do not exist. The present study identifies age and gender-specific CRF distributions in a cancer population. The use of cancer-specific normative CRF data may help stratify initial fitness status and assess improvements in response to exercise interventions in cancer survivors. Data from 703 cancer survivors were analyzed for this study. Quintiles were compiled for peak oxygen consumption (VO2peak), forced vital capacity (FVC), and forced expiratory volume (FEV1) for males and females in 5 age groups (19–39, 40–49, 50–59, 60–69, and ≥70 years of age). VO2peak values for the cancer population were significantly lower than the general US population. The cancer population average in each age group fell within the “very poor” classification of VO2peak values for the general population. FVC values in the cancer population were similar to the general population. Cancer survivors had very low age group-specific VO2peak values compared to the apparently healthy general US population. Previously, CRF values of cancer survivors were compared to normative values for the apparently healthy general population, which yielded imprecise classifications of initial fitness and changes in fitness, resulting in patient discouragement.
Keywords: cancer rehabilitation; population-specific normative values; exercise; cancer treatment side effects